6(2x-3)=2(3x-6)

Simple and best practice solution for 6(2x-3)=2(3x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x-3)=2(3x-6) equation:


Simplifying
6(2x + -3) = 2(3x + -6)

Reorder the terms:
6(-3 + 2x) = 2(3x + -6)
(-3 * 6 + 2x * 6) = 2(3x + -6)
(-18 + 12x) = 2(3x + -6)

Reorder the terms:
-18 + 12x = 2(-6 + 3x)
-18 + 12x = (-6 * 2 + 3x * 2)
-18 + 12x = (-12 + 6x)

Solving
-18 + 12x = -12 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-18 + 12x + -6x = -12 + 6x + -6x

Combine like terms: 12x + -6x = 6x
-18 + 6x = -12 + 6x + -6x

Combine like terms: 6x + -6x = 0
-18 + 6x = -12 + 0
-18 + 6x = -12

Add '18' to each side of the equation.
-18 + 18 + 6x = -12 + 18

Combine like terms: -18 + 18 = 0
0 + 6x = -12 + 18
6x = -12 + 18

Combine like terms: -12 + 18 = 6
6x = 6

Divide each side by '6'.
x = 1

Simplifying
x = 1

See similar equations:

| 89+65= | | 2x-8=14-9x | | 5x+35=12x-35 | | -(4x-(-2x-(3x+6)))=4-(-x+(2x-1)) | | -1.6x+5=-7.8 | | 4(2x+3)=60 | | (6xy^3+cos(y))dx+(2kx^2y^2-xsin(y))dy=0 | | 21=2x+13 | | 5t(t+1)=20 | | n+13=x | | 3x-3=x+4 | | -2(v-8)=4v+4 | | n+13= | | 44=2x-6 | | 4(2n-1)=3(4n+8) | | 5+3(n+2)=n-5 | | y=C(x+3)+1 | | 4(n+3)=60 | | b=mf | | x-7=10*5 | | (4a-5)(5a+4)= | | 3x-4=x+30 | | -3x+3=8-(3x+5) | | -3/8+8= | | 9x+4=6(x-4)+4 | | (x-4)+7=2x-14 | | x=-4.4 | | 0=-16x^2+18x+2 | | 2m+5=10solve | | z^2+10z+25= | | b^2-b+6=0 | | 115+x=204 |

Equations solver categories